2005
DOI: 10.7326/0003-4819-142-4-200502150-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Smoking Cessation Intervention on 14.5-Year Mortality

Abstract: Smoking cessation intervention programs can have a substantial effect on subsequent mortality, even when successful in a minority of participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
507
2
47

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,109 publications
(569 citation statements)
references
References 113 publications
13
507
2
47
Order By: Relevance
“…There is some evidence for a benefit of smoking cessation for specific causes of death in other populations. In the Lung Health study, which comprised individuals who were, on average, heavy smokers with evidence of airway obstruction, mortality rates fell progressively from those who continued to smoke, to intermittent quitters and to those who successfully stopped smoking 29. This pattern was seen for deaths due to coronary heart disease, CVD, and lung cancer (but not other forms of cancer).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for a benefit of smoking cessation for specific causes of death in other populations. In the Lung Health study, which comprised individuals who were, on average, heavy smokers with evidence of airway obstruction, mortality rates fell progressively from those who continued to smoke, to intermittent quitters and to those who successfully stopped smoking 29. This pattern was seen for deaths due to coronary heart disease, CVD, and lung cancer (but not other forms of cancer).…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of risks (1 st step): Smoking cessation significantly decelerates the declination in lung function 4,5,56,57 . In contrast, it has been clearly demonstrated that continuing exposure to smoke considerably accelerates disease progression, independently of its initial stage 12,57 .…”
Section: Treatment Strategymentioning
confidence: 99%
“…Smoking cessation interventions have proved beneficial even in patients with severe COPD (ref. 56 ).…”
Section: Treatment Strategymentioning
confidence: 99%
“…If a smoking habit stops before 30 years of age, the mortality from lung cancer decreases to values similar to those for the population that never smoked. [11][12][13][14] A tobacco addicted patient requires comprehensive management with cognitive behavioral therapy and, at times, medication management. This strategy allows the patient to revert his or her learning of smoking as a coping mechanism and modifies what the smoker thinks and does.…”
Section: Introductionmentioning
confidence: 99%